2020
DOI: 10.3390/fermentation6030079
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Sources Added to Must: Effect on the Fermentations and on the Tempranillo Red Wine Quality

Abstract: Nitrogen supplementation in musts or during the alcoholic fermentation is a common practice to promote fermentations. In this study, the impact of the supplementation of two different sources of nitrogen during Tempranillo red wine elaboration was studied. Mineral and organic nitrogen was added after the exponential yeast growth phase and during winemaking, examining its impact on the alcoholic and malolactic fermentation development, on the aromatic wine composition and on the nitrogenous wine composition. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…N availability has been also indicated as a lever for YAN concentration in grapes (Pérez-Álvarez et al, 2015). In our study, YAN was generally lower than the recommended values (140-150 mg l -1 ) (Santamaría et al, 2020) and we found significant differences across treatments only in 2019. Spontaneous groundcovers showed the highest and the lowest YAN in 2018 and 2019, respectively.…”
Section: Groundcovers Modulate Must Quality But Without Consistently ...supporting
confidence: 37%
“…N availability has been also indicated as a lever for YAN concentration in grapes (Pérez-Álvarez et al, 2015). In our study, YAN was generally lower than the recommended values (140-150 mg l -1 ) (Santamaría et al, 2020) and we found significant differences across treatments only in 2019. Spontaneous groundcovers showed the highest and the lowest YAN in 2018 and 2019, respectively.…”
Section: Groundcovers Modulate Must Quality But Without Consistently ...supporting
confidence: 37%
“…Consequently, the maximum YAN concentration achievable is not very far, and this does not pose an issue, as the objective for winemaking purposes, is to attain a minimum YAN concentration (usually, 150 mg•L −1 ) that allows successful fermentations rather than a maximum YAN concentration. In fact, being under maximum achievable YAN values is adequate, because high nitrogen contents could be detrimental to the must quality for winemaking [17], and if, whatever the case, YAN is found to be too low, musts may be readily fortifed with N in the winery [66].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning nitrogen sources, essential for biomass production and efficient fermentation, a wide variety of compounds assimilable by yeasts are also present in grape musts. Among them, amino acids or ammonium are generally the primary ones (Santamaría et al, 2020), but there are also minor sources like urea, small peptides and ornithine, etc. As expected, the genes that ensure the assimilation of ammonium in glutamate and glutamine were identified in I. terricola.…”
Section: Carbon and Nitrogen Metabolismmentioning
confidence: 99%